Factors Affecting the Profitability of Azerbaijan Banking System - Nuriyeva, Zülfiyye (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The financial services industry varies day by day and the evaluation of the profitability of the financial institution become an important aspect in nowadays. Banks are the integral part of the financial market, and in order to stay at that level necessary to determine how banks operate and what factors affect their profitability. This thesis investigates factors influencing the profitability of banks in Azerbaijan. The external and internal factors were reviewed, and the relationship between these factors and the profitability of Azerbaijan banks were hypothesized. The history and the current performance of the banking sector in Azerbaijan were considered and described in details. The previous studies from many countries in the field of the profitability and factors affecting on it were also considered. The CAMEL ratings have identified the major aspect of the profitability of the commercial banks of Azerbaijan by taking into consideration the capital adequacy, asset quality ratio, management quality ratio, earning ability ratio, liquidity ratio, GDP and size of the banks. The secondary data were collected from the official websites of the banks’ financial reports for period since 2006 until 2012. The modification of the dependent and independent variables of the regression model were displayed by using the Panel Data Analysis Method. The empirical analysis and the results based on the panel data were employed to find the factors influencing the profitability of the banks. Keywords: Profitability, Internal Factors, External Factors, Banking System, Azerbaijan, Panel Data, CAMEL Rating. ………………………………………………………………………………………………………………………… ÖZ: Finans hizmetleri endüstrisi günden günde değişmektedir ve finansal bir kurumun karlılığının değerlendirilmesi günümüzde çok önemli hale gelmiştir. Bankalar finansal pazarın içine geçmiş bir parçasıdırlar ve bu seviyede kalmak için bankaların nasıl çalıştığını ve karlılıklarını hangi faktörlerin etkilediğini belirlemek gerekir. Bu çalışma, Azerbaycan’daki bankaların karlılığını etkileyen faktörleri incelemektedir. İç ve dış etkenler incelenmiş ve bu faktörler arasındaki ilişkilerle bankaların karlılık durumları varsayılmıştır. Azerbaycan’daki bankacılık sektörünün tarihi ve mevcut üretkenliği göz önünde bulundurularak detaylı bir şekilde anlatılmıştır. Önceden birçok ülkede karlılık ve karlılığı etkileyen unsurlar üzerine yapılan çalışmalar da göz önünde bulundurulmuştur. Boyutları, likidite oranlarını, sermaye yeterliliğini, yönetim oranını, kazanç oranını, varlık kalite oranını, pazar oranına hassasiyeti, GSYİH, vs. değerlendirilerek CAMELS yöntemi ölçütleriyle Azerbaycan’daki ulusal ve ticari bankaların karlılıklarının ana boyutları belirlenmiştir. İkincil veriler 2006 yılından 2012 yılına kadar olan süreçteki bankaların finansal raporlarının internet sitelerinden toplanmıştır. Regresyon modelinin bağımlı ve bağımsız değişkenlerinde yapılan değişiklikler Panel Veri Analiz Yöntem’i kullanılarak gösterilmiştir. Deneysel analiz ve panel verilerinden elde edilen sonuçlar bankaların karlılıklarını etkileyen faktörleri bulmak için kullanılmıştır. Anahtar kelimeler: Karlılık, İç Etkenler, Dış Etkenler, Bankacılık Sistemi, Azerbaycan, Panel Veri, CAMEL ölçütleri.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2014. Supervisor: Assoc. Prof. Dr. Nesrin Özataç.
Keywords: Banking and Finance; Banks and Banking - Azerbaijan; Profitability, Internal Factors, External Factors, Banking System, Azerbaijan, Panel Data, CAMEL Rating